2005
DOI: 10.1191/0960327105ht530oa
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of pentacyclic triterpene, lupeol and its ester on cyclophosphamide-induced oxidative stress

Abstract: Cyclophosphamide (CP), an alkylating agent widely used in cancer chemotherapy, causes fatal cardiotoxicity. In the present study, lupeol, a pentacyclic triterpene, isolated from Crataeva nurvala stem bark and its ester, lupeol linoleate were investigated for their possible cardioprotective effects against CP-induced toxicity. Male albino rats of Wistar strain were injected with a single dose of CP (200 mg/kg body weight, ip). In CP-administered rats, activities of lactate dehydrogenase and creatine ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 30 publications
5
39
0
1
Order By: Relevance
“…Rapidly dividing spermatogonia are more sensitive to damage compared with later stage cells. Commonly used chemotherapy agents that have gonadotoxic properties include cisplatin (73), cyclophosphamide (74), and doxyrubicin (75). Heat shock proteins may facilitate the testicular OS response (76).…”
Section: Etiologies Of Oxidative Stressmentioning
confidence: 99%
“…Rapidly dividing spermatogonia are more sensitive to damage compared with later stage cells. Commonly used chemotherapy agents that have gonadotoxic properties include cisplatin (73), cyclophosphamide (74), and doxyrubicin (75). Heat shock proteins may facilitate the testicular OS response (76).…”
Section: Etiologies Of Oxidative Stressmentioning
confidence: 99%
“…Therefore amalgamation of treatment regimen with effective antioxidants might be the desirable approach to alleviate the toxicity induced by CP [21,22]. Various studies have reported that plant extracts possessing antioxidant activity protect against hepatotoxicity induced by CP [23,24].…”
Section: Introductionmentioning
confidence: 98%
“…44,45 Lupeol alleviated the cyclophosphamideinduced increase in the activities of lysosomal hydrolases in serum and heart, and concomitantly increased the levels of cellular thiols. 46 Lupeol increased the activities of TCA cycle enzymes and mitochondrial complexes of electron transport chain in the cardiac tissue 47 and normalized the activities of ATPases, urea, uric acid, and creatinine.…”
Section: Protective Effects Of Bael and Its Phytochemicals Against Thmentioning
confidence: 99%